Islamic pricing benchmarking - Omar, Mohd. Azmi; Mohd Noor, Azman; Meera, Ahamed Kameel Mydin; Abdul Manap, Turkhan Ali; Abdul Majid, M. Shabri; Syed Mohd Zain, Sharifah Raihan; Sarif, Md Ali (ISRA, 2010)
The Islamic finance and banking industry has developed tremendously in recent years. The viability of this industry as an alternative method of investment can no longer be denied. As the current global economic and financial crisis laid bare the systemic problems of conventional finance, the Islamic financial system has been offered as a solution by its proponents. However, Islamic finance has been using conventional finance benchmarks, such as KLIBOR, COFI, LIBOR, etc. to determine its own cost of funds, and hence its return on financial investments. This is so because Islamic finance, if not part of the existing conventional finance, has always served as a financial intermediary for surplus and deficit units. Islamic banking, as the dominant institution in the Islamic finance industry, has gone beyond the function of a financial intermediary, for it also serves as a wakel, custodian, partner, entrepreneur, and guarantor. Nonetheless, Islamic finance has yet to come up with an alternative Islamic Pricing Benchmark (IPB) to determine its cost of capital. The need for having such an IPB for Islamic finance cannot be overemphasized; that would make it more comprehensive and independent from the conventional benchmarks that rely on interest rates, the very thing that Islamic finance abhors. Therefore, this project aims to develop an Islamic pricing benchmark model for the Islamic banking industry, more specifically for Malaysia,given its prominence in the Islamic finance industry. The project has reviewed the Shariah perspective on an Islamic pricing benchmark and has also examined the conventional pricing benchmark being used by banks. The paper further discusses the theoretical formulation of an Islamic benchmark. Thereafter, using sectoral industry and macroeconomic data, it tests the viability of the benchmark using simulation.